Adherence to Bisphosphonates among People Admitted to an Orthopaedic and Geriatric Ward at a University Hospital in Sweden - Abramsson, Linnea (Pharmacy (Basel), 2018)
Oral bisphosphonates are the first choice of therapy to reduce the risk of osteoporotic fractures. These medications have generally poor oral bioavailability, which may further be reduced by concomitant intake of certain foods and drugs; therefore, it is vital to follow specific instructions. The aim with this study was to assess general adherence to oral bisphosphonates and adherence to specific administration instructions among people admitted to two wards at Umeå University hospital in Sweden. This interview study focuses on elderly patients living at home and prescribed oral bisphosphonates. Invited were 27 patients admitted to an orthopaedic ward and a geriatric ward during the period 28 March 2017 and 5 December 2017. In total, 21 patients were interviewed regarding their adherence to oral bisphosphonates. Out of 21 patients, 13 (62%) were considered non-adherent. The most common reason was calcium intake less than 2 h after oral administration of bisphosphonate (54%). The number of regularly prescribed drugs was significantly higher among patients rated non-adherent to bisphosphonates compared to those rated adherent (p = 0.004). Adherence to bisphosphonates administration instruction among elderly people living at home was limited. More research is needed to confirm these results and to investigate the reasons for non-adherence and how adherence to bisphosphonates can be improved.